Embracing a Nurse-Driven Alcohol Withdrawal Protocol Through Quality Improvement. Issue 4 (October 2016) - Barrett, John; Jansen, Maria; Cooper, April; Felbinger, Matthew; Waters, Faith
Abstract: Background: Alcohol withdrawal can lead to severe complications including seizures, delirium tremens, and death if not treated appropriately. Nurses are critical to the safety and outcomes of these patients. Objective: The objective of this retrospective study was to determine if nursing education on a community hospital's alcohol withdrawal protocol led to improved nursing compliance. Methods: This is a quality improvement project involving a two-part retrospective review—an initial needs assessment followed by nursing education and a subsequent posteducation retrospective review. The initial needs assessment included 65 patients. The subsequent posteducation group included 50 patients. Results: Nursing compliance of 1-hour assessments increased after the educational intervention; however, there was no statistically significant difference in 6-hour assessment or medication administration protocol compliance between preeducation and posteducation groups. Conclusion: Nursing education is a good place to start in improving compliance with an alcohol withdrawal protocol, but physicians need to be included to increase standardization within the institution. Future study should look at the effectiveness of different assessment frequency intervals and its impact on patient-centered outcomes.